1986
DOI: 10.1111/j.1529-8817.1986.tb00034.x
|View full text |Cite
|
Sign up to set email alerts
|

COMPARATIVE ELECTROPHORETIC ANALYSIS OF TWO BINLJCLEATE DINOFLAGELLATES1

Abstract: Although two clonal isolates of two different binucleate dinoflagellates Peridinium balticum (Levander) Letnmermann and Glcnodinium foliaceum Stein share a number of unique biochemical and ultrastructural attributes, comparative analysis for sixteen isozyme systems shows that these isolates are quite distinct from each other. Of the 129 different isozyme bands observed, only 28 were common to both organisms. These results support the contention based on plate tabulations that these two isolates should be place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…If this is the case, we must assume that endosymbiotic event and subsequent loss of the original chloroplasts had occurred independently in these dinoflagellates. The electrophoretic data which compared several isoenzymes of P. bahicum and G. foliaceum (Whitten and Hayhome 1986) revealed that these two taxa are genetically not closely related. In this connection, one must also take into account the fact that these three species have quite different arrangements of the thecal plates.…”
Section: Discussionmentioning
confidence: 95%
“…If this is the case, we must assume that endosymbiotic event and subsequent loss of the original chloroplasts had occurred independently in these dinoflagellates. The electrophoretic data which compared several isoenzymes of P. bahicum and G. foliaceum (Whitten and Hayhome 1986) revealed that these two taxa are genetically not closely related. In this connection, one must also take into account the fact that these three species have quite different arrangements of the thecal plates.…”
Section: Discussionmentioning
confidence: 95%
“…Because there was a sequence divergence of about 1% between them, which might be large enough to consider them unrelated, they also believed that molecular data from similar diatom‐harboring dinoflagellates are needed for clear conclusions. Whitten and Hayhome (1986), comparing electrophoretic data using 16 isozyme systems, postulated several different possible adaptations between host and endosymbiont in K. foliaceum (as G. foliaceum ) and D. baltica (as P. balticum ). Morris et al (1993), using data of the histones of the endosymbiont nuclei from K. foliaceum (as G. foliaceum) and D. baltica (as P. balticum ), interpreted that two dinoflagellates acquired their endosymbiont independently (although they did not rule out other possibilities).…”
Section: Discussionmentioning
confidence: 99%
“…50 fiE,m-2,s-t from cool white fluorescent bulbs). Cells were harvested, sonicated, and protein extracts were prepared using the methods of Whitten and Hayhome (1986). Vertical slab polyacrylamide gel electrophoresis of enzymes was performed on the extracts according to Hayhome and Pfiester (1983).…”
Section: Methodsmentioning
confidence: 99%